2022
DOI: 10.1097/phh.0000000000001679
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Responding to COVID-19 Misinformation in a Social Media Feed

Abstract: Misinformation can undermine public health recommendations. Our team evaluated a 9-week social media campaign promoting COVID-19 prevention to mothers (n = 303) of teen daughters in January-March 2021. We implemented an epidemiological model for monitoring, diagnosing, and responding quickly to misinformation from mothers. Overall, 54 comments out of 1617 total comments (3.3%) from 20 mothers (6.6% of sample) contained misinformation. Misinformation was presented in direct statements and indirectly as hypothet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The value of building rapport and trust during a HCP's interaction with a patient should not be underestimated; not only does it lead to improved patient outcomes (Birkhäuer et al, 2017;Chandra et al, 2018;Zachariae et al, 2003), it could also help to sustain a longer-term relationship over time during which the HCP has more opportunities to advise the patient (Healy & Pickering, 2011). In a previous study that used affirmation in responding to participants' misinformed negative vaccination comments within a Facebook group (but did not compare it with a no-affirmation condition), qualitative data showed that some participants revised their beliefs (Buller et al, 2022). Critically, none of the participants left that Facebook group after the affirming refutations, suggesting a willingness to continue engaging that would provide room for follow up and further belief change over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of building rapport and trust during a HCP's interaction with a patient should not be underestimated; not only does it lead to improved patient outcomes (Birkhäuer et al, 2017;Chandra et al, 2018;Zachariae et al, 2003), it could also help to sustain a longer-term relationship over time during which the HCP has more opportunities to advise the patient (Healy & Pickering, 2011). In a previous study that used affirmation in responding to participants' misinformed negative vaccination comments within a Facebook group (but did not compare it with a no-affirmation condition), qualitative data showed that some participants revised their beliefs (Buller et al, 2022). Critically, none of the participants left that Facebook group after the affirming refutations, suggesting a willingness to continue engaging that would provide room for follow up and further belief change over time.…”
Section: Discussionmentioning
confidence: 99%
“…An affirmation allows the HCP to show they understand and care about the patient's concern, which can build trust even between individuals who hold opposing views (Zlatev, 2019). Responding with affirmations may also support a positive response to and continued engagement with the information provider (Buller et al, 2022). We therefore tested whether a HCP providing an affirmation, compared to one who did not, would receive a better reception, even if the HCP subsequently seeks to refute the patient's misconceptions.…”
Section: Empathetic Refutational Interviewmentioning
confidence: 99%
“…Orientation to private groups will be self-explanatory. The community manager will stress respect for others; monitor comments; and correct inappropriate, unfavorable, or bullying comments or misinformation [ 48 ]. Servers will be compensated US $50 for joining the WayToServe Plus Facebook private group.…”
Section: Methodsmentioning
confidence: 99%
“…An affirmation allows the HCP to show they understand and care about the patient's concern, which can build trust even between individuals who hold opposing views (Zlatev, 2019). Responding with affirmations may also support a positive response to and continued engagement with the information provider (Buller et al, 2022). We therefore tested whether an HCP providing an affirmation, compared to one who did not, would receive a better reception, even when the HCP subsequently seeks to refute the patient's misconceptions.…”
mentioning
confidence: 99%